2019
DOI: 10.5194/hess-23-3807-2019
|View full text |Cite
|
Sign up to set email alerts
|

A topographic index explaining hydrological similarity by accounting for the joint controls of runoff formation

Abstract: Abstract. Surface topography is an important source of information about the functioning and form of a hydrological landscape. Because of its key role in explaining hydrological processes and structures, and also because of its wide availability at good resolution in the form of digital elevation models (DEMs), it is frequently used to inform hydrological analyses. Not surprisingly, several hydrological indices and models have been proposed for linking geomorphic properties of a landscape with its hydrological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 68 publications
(85 reference statements)
1
30
0
Order By: Relevance
“…From the outset, we recognise that flow in both surface water and groundwater systems is controlled by the interplay of potential energy differences, usually expressed as potential gradients, and frictional losses, which dissipate a substantial part of the driving energy difference along the flow path into heat. Overland and channel flows are driven by topographygravitational potential energy differencesand it is well known that only a tiny amount of the driving energy difference is converted into kinetic energy of overland or channel flow (Loritz et al, 2019), while more than 99% is dissipated along the hillslope or in the channel. Frictional losses are essentially turbulent, thus proportional to the square of the fluid velocity, and occur mainly at the contact line between the fluid and the solid (the land surface or the wetted perimeter of the rill or the channel cross section), while internal fluid friction is small.…”
Section: Two Water Worlds -Unique Different and Similarmentioning
confidence: 99%
“…From the outset, we recognise that flow in both surface water and groundwater systems is controlled by the interplay of potential energy differences, usually expressed as potential gradients, and frictional losses, which dissipate a substantial part of the driving energy difference along the flow path into heat. Overland and channel flows are driven by topographygravitational potential energy differencesand it is well known that only a tiny amount of the driving energy difference is converted into kinetic energy of overland or channel flow (Loritz et al, 2019), while more than 99% is dissipated along the hillslope or in the channel. Frictional losses are essentially turbulent, thus proportional to the square of the fluid velocity, and occur mainly at the contact line between the fluid and the solid (the land surface or the wetted perimeter of the rill or the channel cross section), while internal fluid friction is small.…”
Section: Two Water Worlds -Unique Different and Similarmentioning
confidence: 99%
“…They particularly allow the exploration of how distributed patterns and their spatial organization jointly control distributed state dynamics and integral behaviour of hydrological systems (Zehe and Blöschl, 2004). Related studies include the investigation of (a) how changes in agricultural practices affect the streamflow generation in a catchment (Pérez et al, 2011), (b) the role of bedrock topography for runoff generation (Hopp and McDonnell, 2009) at the Panola hillslope and the Colpach catchment (Loritz et al, 2017), and (c) the role of vertical and lateral preferential flow networks on subsurface water flow and solute transport at the hillslope scale (Bishop et al, 2015;2014;Zehe, 2011, 2010), including the issue of equifinality. Setting up a physically based model, however, requires an enormous amount of highly resolved spatial data, particularly on subsurface characteristics.…”
Section: Bottom-up Modelling Of the Catchment Water Balancementioning
confidence: 99%
“…The residual soil water content is not available for plants, as it is generally stored in fine pores subject to very high capillary forces. Isotopic tracers have been fundamental to unravelling water flow paths in soils, using dual plots (Benettin et al, 2018;Sprenger et al, 2018), and to distinguishing soil water that is recycled to the atmosphere and released as streamflow (Brooks et al, 2010;McDonnell, 2014).…”
Section: Distributed Solute Transport Modelling -The Key Role Of the mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the use of SWI could be more recommended for the soil moisture representation. Loritz et al (2019) discussed hydrologic similarity in different catchments comparing TWI and HAND performance, and concluded that despite the similarities between these indices, they represent different hydrological aspects, where the modified-HAND version performed better than TWI and HAND approaches. Contrary to their study, the present study showed that HAND was the worst index to represent soil moisture patters.…”
Section: Linear Correlation Of Soil-moisture Spatial Distribution Witmentioning
confidence: 99%